O cuidado e a espiritualidade na perspectiva do ensino religioso e BNCC a partir da conceituação do professor Leonardo Boff - Vanderlei, Davi Jorge Duque (2022)
This text, linked to the research line of Education and Religion of the postgraduate studies in science of religions at the Federal University of Paraíba (UFPB), with the theme: care and spirituality in the perspective of Religious Education and BNCC from the conceptualization of the Professor Leonardo Boff, aims to present the ER at BNCC and its relationship with care and spirituality. This was effected by enabling an approximation between the concepts of care and spirituality, based on Professor Leonardo Boff's vision and the premises that are expressed in religious education at the BNCC. Initially, we present the history of religious education, for that, a bibliographic review was carried out, exploring the main publications available. Consequently, it focused on the study of the main particularities inherent to religious education in Brazil, especially in relation to care and spirituality. Therefore, the text makes a qualitative analysis of religious education, approaching the phases of this teaching in each historical period (colonial, imperial, republican and contemporaneity), raising the pedagogical approach of each phase, intertwining with the definition of care and spirituality to from their respective content, specifically presented in the National Curricular Common Base (BNCC). Therefore, a descriptive-qualitative method was explored, aiming at the evaluation of the main implications and premises associated with religious teaching, care and spirituality in the Brazilian teaching environment. In addition, it was possible to bring concepts according to professor and writer Leonardo Boff in relation to care and spirituality, thus presenting national religious education and its methodological evolution in connection with the concepts of care and spirituality, seeking an approach beyond proselytism. Therefore, it was possible to demonstrate the correlation between religious education in the BNCC with care and spirituality, thus ensuring respect for religious diversity and ensuring the integrality of different beliefs. The insertion of care and spirituality in the school space is still a controversial subject in Brazil. In order for the didactic-pedagogical limitations that are preventing the insertion of care and spirituality in the perspective of religious teaching to be eliminated, it was necessary to base a new set of axioms that would make it possible, a radical change that implies a very complex paradigmatic turnaround.